2020
DOI: 10.1186/s12906-020-03140-x
|View full text |Cite
|
Sign up to set email alerts
|

Findings from a three-round Delphi study: essential topics for interprofessional training on complementary and integrative medicine

Abstract: Background Integrating complementary medicine into medical care promotes patient-oriented care. A well-informed and collaborative professional healthcare team is essential for effective and patient-safe implementation of these methods. At present, the skills for patient counseling, therapy and care regarding complementary medicine vary among the professional groups involved. Professionals generally feel that they are not sufficiently qualified in this area. Curricular concepts for Complementary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…The authors of the present study wanted to report proven treatment options, which might be considered in some patient cases, so that patient safety and well-being can be guaranteed. In addition, the framework of Kneipp has been in use for many years, especially in German-speaking countries, and has also become an established system in academic teaching of complementary therapies [ 126 , 127 ]. For collating and assembling the results from the expert symposium and the many study references, the authors found this classification system very useful, as every expert recommendation or study reference could be assigned to one of the 13 categories.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors of the present study wanted to report proven treatment options, which might be considered in some patient cases, so that patient safety and well-being can be guaranteed. In addition, the framework of Kneipp has been in use for many years, especially in German-speaking countries, and has also become an established system in academic teaching of complementary therapies [ 126 , 127 ]. For collating and assembling the results from the expert symposium and the many study references, the authors found this classification system very useful, as every expert recommendation or study reference could be assigned to one of the 13 categories.…”
Section: Discussionmentioning
confidence: 99%
“…Three of the five Kneipp’s pillars have been presented as the top treatment options, as there has been much evidence identified for those pillars. Interested healthcare professionals might start by engaging themselves with a basic training in the five pillars of classical natural therapies on which the naturopathic health concept according to Kneipp is based [ 126 , 127 ].…”
Section: Discussionmentioning
confidence: 99%
“…Post-fellowship recognition considers the acquisition of knowledge and skills to meet prescribed competency outcomes, plus mastery through clinical experience. The IM Contextual Unit within the RACGP Curriculum 6 offers potential guidance, as does the extensive work that has been undertaken internationally to establish core competencies for IM physicians, 24,25 including GPs. [26][27][28] Considerable support was expressed for advancing the recognition of IM as a sub-specialty within conventional healthcare.…”
Section: Discussionmentioning
confidence: 99%
“…What is considered consensus must be agreed by the researchers at the start of the study, based on the aims of research [44,46]. Consensus building workshops, after rounds, can be used to develop and refine new models and theory [48,54,55]. Workshops can minimise the common critique (that it does not allow for debate [56]) of the Delphi methodology by holding space for respondents to elaborate on their thoughts.…”
Section: The Delphi Methodology Overviewmentioning
confidence: 99%
“…In total, 10 Panel Members were involved in rounds 1 and 9 panel members were involved in both rounds 2 and 3. In Delphi methodology, a diminished number of respondents is expected between rounds [54]. In the case of this research collection a panel member sadly passed-away during the time frame between rounds 1 and 2.…”
Section: Recruitment Strategymentioning
confidence: 99%